Chest wall reconstruction using Latismus Dorsi Flap: our experience - Mittal, S.; Singh, B.; Uppal, M. S.; Mannan, R. (International Surgery Journal, 2017)
Background: Covering a big chest wall defect is the main clinical issue in cancer resection whether it is due to locally advanced breast cancer or any other carcinomas extending to chest wall or injuries leading to chest wall defect. The main aim of the study was to discuss the role of latissmus dorsi flap in chest wall reconstruction. Methods: Study reviewed 15 patients with chest wall defect within a period of two years January 2015 - December 2016, who underwent chest wall reconstruction after tumor resection or burns. Results: Among 15 patients, 12 patients were having locally advanced breast tumors, only one patient with recurrent desmoids tumor of abdominal tumor of abdominal wall extending to chest wall and 2 cases were of electrical burn injuries. The age range varied from 40-60 years. Among these patients 13 were females and 2 were males. The defect size varied from 12x15 cm to 26 x 20 cm. There were no major complications except for partial graft loss in two patients. Conclusions: Lattissmus Dorsi flap is safe and very good flap for chest wall reconstruction.